Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Hasil Belajar Fisika Pada Materi Cahaya Kleas VIII SMP Negeri 2 Tambusai TP. 2020/2021 - Januaris Pane; Eliza Ernita Manurung; Juliper Nainggolan (STKIP PGRI SITUBONDO, 2021)
This study aims to determine the effect of PBL on physics learning outcomes in light material at SMP Negeri 2 Tambusai. The method used in this study is a quasi-experimental method with the research population being class VIII students of SMP Negeri 2 Tambusai and the sample in this study was 50 students. The sampling technique used is purposive sampling. The experimental class (VIII1) research sample was obtained using the PBL model and the control class (VIII2) using the conventional model. The instrument used is a test of learning outcomes in the form of multiple-choice as many as 20 questions. before receiving treatment for the two samples, the experimental class pretest average score was 38.80 with a standard deviation of 13.87 and in the control class the average value was 38.20 and the standard deviation was 11.26. After doing different studies, the average posttest score for the experimental class was 71.00 and in the control class the average score was 65.80 and the standard deviation was 9.97. the results of the pretest and posttest data prerequisite test stated that the sample had normality and homogeneity distribution. then a one-sided t-test (α=0,05) and a simple regression test were performed. from the results of one-party t-test, namely thitung> ttabel (1,761 > 1,677) with a significant level of 0.042. and for the results of the simple regression test Y = 24,64+0,61X . in the equation the linear regression direction coefficient (b)=0.61 indicates that if student activity increases by 1, student learning outcomes will increase by 0.61. it is concluded that there is a significant effect of the PBL model on the learning outcomes of class VIII students of SMP Negeri 2 Tambusai in the academic year 2020/2021